DUKUNGAN SOSIAL PADA IBU USIA REMAJA DALAM PENGASUHAN ANAK USIA INFANT: SOCIAL SUPPORT TO ADOLESCENT MOTHERS IN INFANT AGE CHILDREN CARE - Diana Dayaningsih; Erni Suprapti; Feri Tri Y; Aprillya Dwi S (JURNAL KEPERAWATAN SISTHANA, 2020)
Teenage pregnancy and parenthood among teenagers are still a matter of international concern because of the potential adverse consequences for society, families and individuals. Teen pregnancies are more than 80% unplanned. The transition to parenting experienced by teens creates a period of instability that demands new parenting roles. Parenting by adolescent mothers will be more effective when adolescent mothers receive strong social and emotional support from their families and partners. The purpose of this study was to explore social support for adolescent mothers in the care of infant children. Qualitative research methods with an Interpretative Phenomenological Analysis (IPA) approach. Respondents in this study there were 5 respondents who met the inclusion criteria were taken using purposive sampling technique. The data was obtained using a semi-structured interview method. The research credibility was achieved by using triangulation of sources through interviews with the mothers of the main participants. The results showed that the five participants expressed various experiences of being a mother that varied when caring for infant age children depending on the situation experienced by each mother. Social support for adolescent mothers in child care includes 4 themes, namely 1). Instrumental Support, 2). Information Support, 3). Financial Support, 4). Emotional Support Based on the results of this study, it is hoped that there will be a special program for adolescent mothers, in which the role of health workers is able to support mothers' efforts to obtain optimal education and skills in parenting.